2014
DOI: 10.5713/ajas.14.0329
|View full text |Cite
|
Sign up to set email alerts
|

Zearalenone Altered the Serum Hormones, Morphologic and Apoptotic Measurements of Genital Organs in Post-weaning Gilts

Abstract: The present study was aimed at investigating the adverse effects of dietary zearalenone (ZEA) (1.1 to 3.2 mg/kg diet) on serum hormones, morphologic and apoptotic measurements of genital organs in post-weaning gilts. A total of twenty gilts (Landrace×Yorkshire×Duroc) weaned at 21 d with an average body weight of 10.36±1.21 kg were used in the study. Gilts were fed a basal diet with an addition of 0, 1.1, 2.0, or 3.2 mg/kg purified ZEA for 18 d ad libitum. Results showed that 3.2 mg/kg ZEA challenged gilts decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 24 publications
3
29
0
Order By: Relevance
“…ZEA also causes genotoxicity via DNA damage (Gao et al, ), DNA adduct formation (Lioi et al, ), and chromosomal abnormalities (El‐Makawy et al, ) among other genetic defects. The teratogenic effect of ZEA has also been shown to cause edemas in the reproductive organs of Gilts (Chen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…ZEA also causes genotoxicity via DNA damage (Gao et al, ), DNA adduct formation (Lioi et al, ), and chromosomal abnormalities (El‐Makawy et al, ) among other genetic defects. The teratogenic effect of ZEA has also been shown to cause edemas in the reproductive organs of Gilts (Chen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the work of Brydl et al [10], the uterine weight of pigs receiving feed contaminated with ZEA was higher in comparison with the control group, and endometrial hyperplasia was observed in the experimental animals. The results of research [11][12][13][14][15] investigating the effects on ZEA and its metabolites on the reproductive organs of animals constitute the basis for human studies. The presence of ZEA and its metabolites was analyzed by Twarużek et al [16] in prostate tissues and by Gadzała-Kopciuch et al [17] in uterine mass tissue (endometrial cancer).…”
Section: Introductionmentioning
confidence: 99%
“…The similar growth rate, feed intake, and feed efficiency of the piglets among all the treatments indicated that gilts within a treatment likely consumed a similar amount of digestible energy and other nutrients, and that differences obtained among treatments were likely attributable to the different concentrations of ZEA in the diet [ 14 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that ZEA at the dietary levels of 20 and 40 µg/kg bw in sexually immature gilts induced experimental hyperestrogenism and stimulated the proliferation of nearly all uterine wall tissues [ 13 ]. Our previous study also showed that ZEA at the dietary concentrations of 1.1 to 3.2 mg/kg increased genital organ size and hyperplasia of submucosal smooth muscles in the corpus uteri of gilts in a dose-dependent manner [ 14 ]. More recently, it has been observed that 1.04 mg/kg ZEA could promote the autocrine action or expression of the ghrelin gene and upregulation of the expression of the proliferating cell nuclear antigen (PCNA) gene in ovary of gilt [ 15 ].…”
Section: Introductionmentioning
confidence: 99%